Comparative Clinical Study of Percutaneous Epididymal Sperm Aspiration and Testicular Biopsy in the Outcome of ICSI-Assisted Fertility Treatment in Patients with Obstructive Azoospermia - Li, Lian; Liao, Hongqing; Li, Meiqing; Xiao, Jianghua; Wu, Lei (Frontiers in Surgery, 2022)
Objective To compare and contrast the effects of percutaneous epididymal sperm aspiration (PESA) and testicular sperm aspiration (TESA) on the outcome of intracytoplasmic sperm injection (ICSI)-assisted fertility treatment in patients with obstructive azoospermia. Methods Patients with obstructive azoospermia with an age distribution of 20–36 years admitted to the male department of the Reproductive Center of the Second Affiliated Hospital of South China University (Hengyang Nanhua Xing Hui Reproductive Health Hospital) from December 2018 to December 2020 were used in this study. One group was set up as the PESA group to perform PESA, and the other group was set up as the TESA group to perform percutaneous testicular biopsy for sperm extraction. Patients who were unsuccessful in PESA continued to undergo TESA, and if sperm were retrieved, they were classified as the TESA group. General information on male patients and their partners was collected and compared in patients from different sperm source groups. Embryo development (normal fertilization rate, high-quality embryo rate, and high-quality blastocyst rate) and pregnancy outcome (clinical pregnancy rate, miscarriage rate, and ectopic pregnancy rate) were compared between the two groups. Results Finally, there were 26 patients in the PESA group and 31 patients in the TESA group. There were no significant differences in terms of age, years of infertility, testosterone level, (FSH) follicle-stimulating hormone level, and testicular volume between the male patients in the PESA and TESA groups of two different sperm sources, and no significant differences were found in the general conditions of the female patients in terms of age, number of eggs obtained, number of sinus follicles, basal FSH value, and basal E2 value (p > 0.05). The rate of high-quality blastocysts in the TESA group was significantly higher than that in the PESA group (p < 0.05); the differences in clinical normal fertilization rate, high-quality embryo rate, clinical pregnancy rate, miscarriage rate, and ectopic pregnancy rate between the two groups were not statistically significant (p > 0.05). Conclusion ICSI with different sources of sperm in patients with male factor infertility alone, which had no significant effect on embryo development, embryo implantation rate, clinical pregnancy rate, and miscarriage rate, resulting in better clinical outcomes.